Distribution of metastatic sites in patients with prostate cancer: A population-based analysis - Gandaglia, Giorgio; Abdollah, Firas; Schiffmann, Jonas; Trudeau, Vincent; Shariat, Shahrokh F.; Kim, Simon P.; Perrotte, Paul; Montorsi, Francesco; Briganti, Alberto; Trinh, Quoc-Dien; Karakiewicz, Pierre I.; Sun, Maxine (The Prostate, 2014)
BACKGROUND There is few data on what constitutes the distribution of metastatic sites in prostate cancer (PCa). The aim of our study was to systematically describe the most common sites of metastases in a contemporary cohort of PCa patients. METHODS Patients with metastatic PCa were ed from the Nationwide Inpatient Sample (1998–2010). Most common metastatic sites within the entire population were described. Stratification was performed according to the presence of single or multiple (≥2 sites) metastases. Additionally, we evaluated the distribution of metastatic sites amongst patients with and without bone metastases. RESULTS Overall, 74,826 patients with metastatic PCa were identified. The most common metastatic sites were bone (84%), distant lymph nodes (10.6%), liver (10.2%), and thorax (9.1%). Overall, 18.4% of patients had multiple metastatic sites involved. When stratifying patients according to the site of metastases, only 19.4% of men with bone metastases had multiple sites involved. Conversely, among patients with lymph nodes, liver, thorax, brain, digestive system, retroperitoneum, and kidney and adrenal gland metastases the proportion of men with multiple sites involved was 43.4%, 76.0%, 76.7%, 73.0%, 52.2%, 60.9%, and 76.4%, respectively. When focusing exclusively on patients with bone metastases, the most common sites of secondary metastases were liver (39.1%), thorax (35.2%), distant lymph nodes (24.6%), and brain (12.4%). CONCLUSIONS Although the majority of patients with metastatic PCa experience bone location, the proportion of patients with atypical metastases is not negligible. These findings might be helpful when planning diagnostic imaging procedures in patients with advanced PCa. Prostate 74:210–216, 2014. © 2013 Wiley Periodicals, Inc.